Incidence of and risk factors for febrile morbidity after laparoscopic-assisted vaginal hysterectomy - Wongpia I; Thinkhamrop J; Seejorn K; Buppasiri P; Luanratanakorn S; Temtanakitpaisan T; Khampitak K (Dove Medical Press, 2014)
Iyara Wongpia, Jadsada Thinkhamrop, Kanok Seejorn, Pranom Buppasiri, Sanguanchoke Luanratanakorn, Teerayut Temtanakitpaisan, Kovit Khampitak Department of Obstetrics and Gynecology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand Background: The purpose of this study was to assess the incidence of and risk factors for postoperative febrile morbidity after laparoscopic-assisted vaginal hysterectomy (LAVH). Methods: This retrospective study was carried out using the medical records of women with benign gynecologic conditions who underwent LAVH between June 2007 and May 2012 at Srinagarind Hospital in Thailand. Data were collected to assess baseline patient characteristics, occurrence of body temperature ≥38°C on two occasions at least 6 hours apart in the 24 hours following the surgical procedure, and possible risk factors related to postoperative febrile morbidity. Results: In total, 199 women underwent LAVH during the study period. They had a mean age of 46±6 years, a mean body mass index of 24.0±3.2 kg/m2, a mean surgical duration of 134±52 minutes, median estimated blood loss of 200 mL, a mean total hospital stay of 5±2 days, and a mean postoperative hospital stay of 3±2 days. Postoperative febrile morbidity was documented in 31 cases (15.6%). The cause of postoperative fever was unknown in most cases, with only two cases having an identifiable cause. The risk of postoperative febrile morbidity was highest in women treated with more than two antibacterial agents and with a regimen of more than 3 days. Conclusion: This study shows a moderately high rate of febrile morbidity after LAVH, for which the main risk factors were use of multiple drugs and doses for antibiotic prophylaxis. Keywords: laparoscopic-assisted vaginal hysterectomy, febrile morbidity, incidence, risk factors